2017
DOI: 10.1037/per0000173
|View full text |Cite
|
Sign up to set email alerts
|

Toward validation of a borderline personality disorder–relevant picture set.

Abstract: This investigation sought to validate a stimulus set previously adapted by expert consensus from the International Affective Picture System to be unpleasant and evocative to individuals with borderline personality disorder (BPD). This set was rated as significantly more arousing by 22 individuals diagnosed with BPD compared to 22 healthy controls, though this mean difference appeared to be driven by differences in ratings for a small subset of pictures. The present BPD sample did not rate the BPD-specific pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Given differing moral concerns, people may simply disagree with each other regarding their moral evaluation of an image, absent any disagreement about what is portrayed in it (i.e., absent any ambiguity). Once again, divisiveness may prove highly useful for specific research goals such as eliciting psychological or physiological responses that are diagnostic of one’s political or moral preferences (e.g., [ 41 , 72 , 163 ]), or developing pictorial measures of individual differences [ 41 , 65 , 66 , 130 , 156 , 164 166 ]. In S5 Text , we present preliminary analyses that attempt to empirically identify images that are divisive with respect to political orientation and gender.…”
Section: Resultsmentioning
confidence: 99%
“…Given differing moral concerns, people may simply disagree with each other regarding their moral evaluation of an image, absent any disagreement about what is portrayed in it (i.e., absent any ambiguity). Once again, divisiveness may prove highly useful for specific research goals such as eliciting psychological or physiological responses that are diagnostic of one’s political or moral preferences (e.g., [ 41 , 72 , 163 ]), or developing pictorial measures of individual differences [ 41 , 65 , 66 , 130 , 156 , 164 166 ]. In S5 Text , we present preliminary analyses that attempt to empirically identify images that are divisive with respect to political orientation and gender.…”
Section: Resultsmentioning
confidence: 99%
“…Participants with BPD reported significantly more subjective arousal during the stimulus exposure than did controls [for details see ( 80 )]. The relationship between BPD symptom severity and mean subjective arousal was of medium effect size ( r = 0.27), but not statistically significant ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The modest sample size limited the study's power to identify statistically significant effects, and replication with larger samples is needed to increase confidence in the pattern of effects found in this study. While the IAPS images used in this study to evoke an emotional response were selected by expert consensus to characterize a range of BPD sensitivities, and participants with BPD in this study reported significantly higher subjective arousal to the pictures than controls, we previously reported that there was heterogeneity across different picture cues in how arousing the present sample rated the stimulus set ( 80 ). More work is needed to build a more consistently challenging stimulus set to increase the potency of the emotionally arousing visual stimuli in future BPD studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given differing moral concerns, people may simply disagree with each other regarding their moral evaluation of an image, absent any disagreement about what is portrayed in it (i.e., absent any ambiguity). Once again, divisiveness may prove highly useful for specific research goals such as eliciting psychological or physiological responses that are diagnostic of one's political or moral preferences (e.g., [41,72,163]), or developing pictorial measures of individual differences [41,65,66,130,156,[164][165][166]. In S5 Text, we present preliminary analyses that attempt to empirically identify images that are divisive with respect to political orientation and gender.…”
Section: Inter-rater Consensusmentioning
confidence: 99%